Bilateral Posterior Fracture Dislocation of Shoulder - Shah, Himanshu; Daveshwar, Rajiv (Nepal Orthopaedic Association Journal, 2013)
Posterior dislocation of shoulder is relatively uncommon entity. Posterior fracture dislocation of shoulder is even rare and bilateral posterior fracture dislocation of shoulder is even rarest entity. We present a case of 45 years of adult male having bilateral posterior fracture dislocation of shoulder following convulsive seizure and treated with open reduction and internal fixation with satisfactory functional outcome. DOI: http://dx.doi.org/10.3126/noaj.v3i1.9324   Nepal Orthopedic Association Journal 2013 Vol.3(1): 31-34